P69 Hepatitis delta RNA level and genotype, and hepatitis B surface antigen titre predict response to PEG-interferon in the treatment of chronic hepatitis delta virus. (16th November 2010) - Hughes, S; Carey, I; Shang, D; Horner, M; Bruce, M; Fletcher, I; Cross, T J S; Suddle, A; Agarwal, K; Harrison, P M
Abstract : Introduction: Hepatitis Delta Virus (HDV) infection is associated with more severe liver disease in individuals with hepatitis B virus (HBV). The only treatment for HDV shown to be of benefit is α-interferon, but predictors of response to therapy are not known. Aim: To evaluate the efficacy of PEG-interferon α 2a (PEG-IFN) therapy and factors predicting viral response in patients with chronic HBV/HDV co-infection. Method: Between 2005 and 2010, 14 patients (71% female, median age 32, 57% Black African, 36% Caucasian, 7% Oriental, 79% HBeAg −ve, 100% HDV RNA +ve, 64% HDV genotype 1, 29% HDV genotype 5, 7% HDV genotype 6, 43% cirrhotic) were treated with PEG-IFN 180 mcg/week for a median of 48 weeks. The median follow-up post treatment was 16.5 months. A retrospective analysis was undertaken to assess clinical and virological factors predictive of outcome. HDV RNA was measured by an in-house real-time quantitative PCR assay (range 6.4×102 to 6.4×107 copies/ml), and genotyping was performed by comparison of nucleotide sequences of HDV RNA with previously reported sequences of HDV genotypes 1–8. HBV DNA was measured using the Roche COBAS Ampliprep/TaqMan assay. Hepatitis B surface antigen (HBsAg) titres were measured using the Abbott Architect assay. Results: In response to PEG-IFN, 64% cleared HDV RNA by end of treatment (EOT), 1 patient with genotype 1 HDV relapsed and 54% remain HDV RNA −ve beyond 24 weeks post-treatment (sustained virological response; SVR); 2 patients subsequently cleared HBsAg. Baseline HDV RNA was significantly higher in non-responders compared to those with SVR (2.1×106 vs 1.3×104 copies/ml, p=0.003) and predicted treatment response (AUROC=1.0, p=0.003). A HDV RNA of >1.96×105 copies/ml predicted treatment failure (p=0.001, positive predictive value 100% and sensitivity 100%). There was a strong correlation between HDV RNA level and HBsAg titre (r=0.82, p<0.001). Baseline HBsAg titre was significantly higher in non-responders compared to those with SVR (10 067 vs 5820 IU/ml, p=0.007) and also predicted treatment response (AUROC 0.95, p=0.007). A cut-off HBsAg titre of >9000 IU/ml predicted treatment failure (p=0.021, positive predictive value 100% and sensitivity of 67%). All patients with HDV genotype non-1 achieved SVR, compared with only 25% of those with HDV genotype 1 (p=0.02). Responders were similar to non-responders with respect to gender, age, liver histology staging and pre-treatment ALT. Conclusion: PEG-IFN was an effective treatment for chronic HDV, with 54% achieving SVR. Levels of HDV RNA >1.96x105 copies/mL and HBsAg titres >9000 IU/ml predicted treatment failure, whereas HDV genotype non-1 predicted long-term viral clearance.